Heat transfer enhancement in a triangular duct using compound nanofluids and turbulators - Ahmed, Hamdi E.; Ahmed, Mirghani Ishak; Yusoff, Mohd Zamri (Elsevier Ltd, 2015)
Numerical and experimental investigation is carried out to study the laminar heat transfer and fluid flow characteristics in an equilateral triangular duct using combined vortex generator and nanofluids. Two different types of nanoparticles "namely Al2O3 and SiO2" suspended in distilled water with two particles concentrations are successfully prepared and experimentally tested. Both numerical and experimental results show a good enhancement in heat transfer by using vortex generator with base fluid. A significant heat transfer enhancement is observed by using compound vortex generators and nanofluids accomplished with a moderate increase in the pressure drop. High gradient in wall temperatures is monitored when the water is replaced by nanofluid particularly at higher volume fraction. A small deviation has been seen between the present numerical and experimental results